Writing In Nursing Education (WINE). - Moni, Roger (Australian Learning and Teaching Council (ALTC), 2010)
The Writing In Nursing Education (WINE) EndNote library consists of 300 references on the learning and teaching of writing. As well as references from nursing journals, hard copy and online resources are included. The enclosed resource can be opened by EndNote